2021
DOI: 10.20473/bhsj.v4i1.26913
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Activity of Ethanol Extract of Noni Leaves (Morinda citrifolia) towards Parasitemia, Splenomegaly, and Hepatomegaly in Plasmodium berghei ANKA Infected Mice

Abstract: Introduction: Malaria is one of the infectious diseases found in tropical countries and sub-tropical countries. In 2016 there were an estimated 445,000 people died to malaria. Alternative medicine is needed, such as natural based ingredient. Morinda citrifolia or noni plant is a medicinal plant found in all parts of Indonesia which has many benefits, such as antibacterial, analgesic, anticancer, antioxidant, and anti-inflammatory. The aims of this study were to determine the antimalarial activity of ethanol ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…2020). Another research also revealed that the alkaloid and flavonoid compounds contained in the ethanol extract of Morinda citrifolia were the main compounds that acted as antiplasmodials against mice infected with P. berghei ANKA (Rahayu, Hernaningsih, & Arwati, 2021).…”
Section: This Is An Open Acces Article Under the Cc-by Licensementioning
confidence: 99%
“…2020). Another research also revealed that the alkaloid and flavonoid compounds contained in the ethanol extract of Morinda citrifolia were the main compounds that acted as antiplasmodials against mice infected with P. berghei ANKA (Rahayu, Hernaningsih, & Arwati, 2021).…”
Section: This Is An Open Acces Article Under the Cc-by Licensementioning
confidence: 99%